Equity participation in financial intermediaries: a new donor instrument in rural finance? A proposal submitted to the International Fund for Agricultural Development, Rome - Hans Dieter Seibel (Universität zu Köln, Arbeitsstelle für Entwicklungsländerforschung (AEF), 2000)
The IFAD Rural Finance Policy lists among the initiatives to be supported commercially-operated apex organizations for refinancing MFIs (para. 20) and stipulates that, Equity financing through appropriate apex institutions may be developed by IFAD as a new instrument, which would provide the much-needed external capital and leverage multiples of domestic capital. (para. 32) Equity participation, which avoids some of the pitfalls of credit lines, strengthens the capital base of apex funds and rural financial institutions and leverages additional domestic resources in the form of savings deposits or additional equity. It may also be used to fulfil legal minimum capital requirement when transforming non-formal institutions into formal entities. (para. 44) Examples given of autonomous apex funds are the Social Capital Fund in Argentina, the Palli Karma-Sahayak Foundation in Bangladesh, and the People?s Credit and Finance Corporation in The Philippines (para.32). IFAD may also invest in larger-size financial intermediaries, among them microenterprise banks and rural banks as well as agricultural development banks and some commercial banks, which either refinance smaller rural financial institutions or lend directly to IFAD?s target group.
Keywords: 330